(untitled) (Journal Of Educational and Psychological Researches, 2014)
Current research aimed at measurement of management of emotional among counselors and knowledge of emotions management according to the variables of sex and length of service with counselors. The Scale applied to a sample of basic research, amounting to (300) counselors. 1- That counselors have administration emotional. 2- There are no differences in the management of emotional statistically significant according to the variable (gender). 3- statistically significant differences according to the variable (length of service) in the management of emotional. 4- statistically significant differences according to the variable (type and length of service) in the management of emotional.